Local environmental problems of urban poor areas: a case study / MJB Moral, Ruslan Rainis and Md. Aminul Islam - Moral, MJB; Rainis, Ruslan; Islam, Md. Aminul (2008)
Environmental conditions have severe impact on the livelihood conditions, health and the security of the poor (Bo jo & Reddy, 2002). It is increasingly recognized that poverty and environment are correlated. Poverty affects environmental conditions and vice versa. It is because a degraded environment will greatly affect the poor. The poor tends to become poorer as the environment conditions degrade. Owing to scarcity of job. hardcore poor households of both study communities migrated to the city and live in low-lying vulnerable and unhygienic spaces where inadequate services persist. Due to these conditions they stiffer during natural hazards such as flood. which expose them to health hazards that reduce their savings and productivity. Conversely because of insufficient services they pollute the neighborhood environment by illegal dumping of wastes and discharging of wastewater. The principal objective of this study was to identify the local environmental problems. The study was undertaken by acquiring primary data from the field survey by employing a structured questionnaire and gathered information with emphasis on poor and their local environment. The head of poor household or a member of each household was used as respondents. it was found that environmental problems such as improper solid waste management, drainage, housing and land title were the persistent problems in the communities.